Political Advertising and Data-Driven Campaigning in Australia - Ridout, Travis N. (2024)
There have been breathtaking accounts of the use of data in political campaigns for microtargeting and message testing, among other practices. Most of these examine presidential campaigns in the US. But evidence speaking to the use of data-driven campaigning (DDC) beyond the US is rather thin. Here I examine the use of DDC in Australia, focusing on political advertising specifically. I interview 15 campaign practitioners, asking about several indicators of DDC, including (a) the extent of ad targeting, (b) tailoring of ads to specific audiences, (c) the use of data analytics in ad targeting/tailoring, (d) efforts at online fundraising, and (e) ad testing. I find considerable variation in the use of DDC that stems from differences in resources, different campaign philosophies, and uncertainties about the data. I also find an important role for marketing agencies in supplementing DDC capabilities.